Nutrient distribution in East Antarctic summer sea ice: a potential iron contribution from glacial basal melt - Duprat, LPADM; Corkill, M; Genovese, C; Townsend, AT; Moreau, S; Meiners, KM; Lannuzel, D (Journal of Geophysical Research: Oceans, 2020)
Antarctic sea ice can incorporate high levels of iron (Fe) during its formation and has been suggested as an important source of this essential micronutrient to Southern Ocean surface waters during the melt season. Over the last decade, a limited number of studies have quantified the Fe pool in Antarctic sea ice, with a focus on late winter and spring. Here we study the distribution of operationally defined dissolved and particulate Fe from nine sites sampled between Wilkes Land and King George V Land during austral summer 2016/2017. Results point toward a net heterotrophic sea‐ice community, consistent with the observed nitrate limitation (−1) which can serve as a hotspot for bacterial activity. Finally, results indicate a potential relationship between glacial meltwater discharged from the Moscow University Ice Shelf and the occurrence of Fe‐rich (∼4.3 μM) platelet ice in its vicinity. As climate change is expected to result in enhanced Fe‐rich glacial discharge and changes in summer sea‐ice extent and quality, the processes influencing Fe distribution in sea ice that persists into summer need to be better constrained.